Is eccentric exercise an effective treatment for lateral epicondylitis? A systematic review - Cullinane, Frances L; Boocock, Mark G; Trevelyan, Fiona C (Clinical rehabilitation, 2014)
Objective: To establish the effectiveness of eccentric exercise as a treatment intervention for lateral epicondylitis. Data sources: ProQuest, Medline via EBSCO, AMED, Scopus, Web of Science, CINAHL. Review methods: A systematic review was undertaken to identify randomized and controlled clinical trials incorporating eccentric exercise as a treatment for patients diagnosed with lateral epicondylitis. Studies were included if: they incorporated eccentric exercise, either in isolation or as part of a multimodal treatment protocol; they assessed at least one functional or disability outcome measure; and the patients had undergone diagnostic testing. The methodological quality of each study was assessed using the Modified Cochrane Musculoskeletal Injuries Group score sheet. Results: Twelve studies met the inclusion criteria. Three were deemed ‘high’ quality, seven were ‘medium’ quality, and two were ‘low’ quality. Eight of the studies were randomized trials investigating a total of 334 subjects. Following treatment, all groups inclusive of eccentric exercise reported decreased pain and improved function and grip strength from baseline. Seven studies reported improvements in pain, function, and/or grip strength for therapy treatments inclusive of eccentric exercise when compared with those excluding eccentric exercise. Only one low-quality study investigated the isolated effects of eccentric exercise for treating lateral epicondylitis and found no significant improvements in pain when compared with other treatments. Conclusion: The majority of consistent findings support the inclusion of eccentric exercise as part of a multimodal therapy programme for improved outcomes in patients with lateral epicondylitis.